Human governance: The art of emotional intelligence of leader through the model of spirituality - Johar, Siti Sarawati (Science Publishing Corporation (SPC), 2018)
This paper is a concept paper which is focused on the discussion about the emotional intelligence of leader in the human governance elements at the workplace from the perspectives of the spirituality model. These are the claims of reality the management application which is based of religion and science as well as browse the dimension of emotional in organizations today. This discussion encompasses the conceptual of emotional intelligence, human governance and spirituality model; application needs; challenges and hopes. In line with the demands of human capital development, supposed the physical development and materially advanced with that momentum growing over the years in tandem with human development. We not only want the country to have a first-class facility, but most important are the mentality, spiritual and behaviour first class which is oriented of human capital. The synonyms here, each employee in any organization as a human entity are should be the ideal capacity of human capital in terms of emotional intelligence to produce the quality work and have a strong human governance. To that end, leaders in the workplace should have a high level of emotional intelligence to form a positive culture among employees and create practices that are consistent so that it can become a habit that is conducive to all parties in the working environment. The end of this paper will demonstrate the need for all leaders to have the emotional intelligence with spiritual strength and lead a more meaningful behaviour. It would also allow employees to perform a dynamic human capital and thus able to establish a framework of a major platform in the management and human governance characterized by spirituality trait in their work.